Analisis Struktur dan Komposisi Vegetasi di Kawasan Hutan Konservasi Suaka Margasatwa Gunung Raya Kecamatan Warkuk Kabupaten OKU Selatan - Suci Suci; Zulkifli Dahlan; Indra Yustian (Faculty of Mathtmatics and Natural Sciences, 2013)
Structure and vegetation Analysis composition in the area used for cultivation of mount forest wild-life conservation of Gunung Raya in Warkuk subdistrict of OKU Selatan regency can describe the plant biodi-versity, abundace, spesies dominance, type and vegetation profile, and the succesion pattern. The vegetation data was from the transek method which is line compartmentalized, namely 3 transek with the 10 plot per sta-tion. The observation was done in every growth of the vegetation which was grouped into four levels, such as seedling and caver plant, sapling, pole and tree. the result showed that the vegetation composition for the tree level in the first station were dominated by Shorea sp (with the important Index Value 36.81%), the pole domi-nated by Syzygium polyanthum, and saplings with dominated by Styrax benzoin and seedlings and cover plants with dominated by Calamus sp. The second station for the tree level which was comprised of five spe-cies of trees with dominated by Litsea mappaceae. While dominated by Homalanthus populneus. The next is the 10 spesies of saplings with 8 families which dominated by Adianthum capillus (with the important index value of 52.55%).